The complete chloroplast genome sequence of Zanthoxylum undulatifolium Hemsl. (Rutaceae). Issue 2 (1st February 2022) - Sun, Chong; Liu, Xia; Zhou, Houlin; Liu, Jing; Li, Xiaoying; Liu, Hailang; He, Can
Abstract: Zanthoxylum undulatifolium is an excellent economic tree species with important medical value. This study reports the first complete chloroplast genome sequence of Z. undulatifolium . Its whole chloroplast genome is 158, 400 bp in length, including a large single-copy (LSC) region of 85, 898 bp, a small single-copy (SSC) region of 17, 610 bp, and two inverted repeat (IR) regions of 27, 446 bp. The chloroplast genome contains a total of 132 genes, comprising 87 protein-coding genes, 37 tRNA genes, and eight rRNA genes. The overall GC content of the chloroplast genome is 38.46%, with the corresponding values in the LSC, SSC, and IR regions are 36.87%, 33.51%, and 42.55%, respectively. Phylogenetic analysis revealed the sister relationship between Z. undulatifolium and Z. bungeanum .